GAYA HIDUP TERHADAP MINAT MENABUNG MAHASISWA SOSIOLOGI FAKULTAS ILMU SOSIAL DAN POLITIK UNIVERSITAS SAM RATULANGI - Rahel, _; Kandowangko, Nicolaas; Lasut, Jouke J. (HOLISTIK, Journal Of Social and Culture, 2020)
Lifestyle can be recognized by looking at how people spend their time (activity), what is important people consider on the environment (interests), and what people think of themselves and the world around (Opinion). Lifestyle is the behavior of a person shown in activities, interests and opinions, especially those related to self-image to reflect on his or her social status. In the community structure, college student are an intellectual generation that is expected to behave in accordance with good norms and values, have moral and knowledge, is also expected to be a development innovator in all aspects, so as to cleanse the inequality that exists in the community. The function that the college student has as Agent of change is an agent that can make changes and as Agent of social control is as an agent in charge of monitoring and control of the Government, to the policies and to other matters undertaken by the Government, all of which are done is none other than and not merely to keep the interests of the people and avoid the people of the wrongdoers committed by the government. Boarding house is a service that offers a room or a place to be settled with a certain amount of payment for each specific period (generally payment per month). So the college student lifestyle is influenced by certain values of religion, culture and social life. Sociolgy Fispol Unsrat college student choose to stay in strategic boarding house and close to campus, living with one campus friends, and close to educational facilities such as Internet café, computer rental, photocopy. Positive lifestyle, responsible, principles, self-reliant, such as doing college activities while having a side job, buying goods as needed, using technology for college needs, using simple room facilities, simple appearance, not easily affected by the outside environment and does not follow the lifestyle of hedonism and consumerism. Keywords: lifestyle, college student, boarding house